The alkaline phosphatase-to-prealbumin ratio combined with CT-quantified sarcopenia predicts survival in gastric cancer patients after surgical resection - Xu, Yunxin; Du, Zhongze; Xue, Yingwei; Song, Hongjiang (Frontiers in Nutrition, 2025)
ObjectivesThe aim of this study was to comparatively evaluate the prognostic efficacy of alkaline phosphatase to prealbumin ratio (APR) against eight established hematological biomarkers. This study pioneered the development of APR-sarcopenia, a novel composite biomarker integrating hematological indices with computed tomography-quantified body composition parameter, and assessed its predictive performance.MethodsThis study included 190 gastric cancer patients who underwent surgery and had computed tomography (CT) scans at our institution between January 2016 and December 2017. Comprehensive clinical data were available for all patients. Differences in clinical and pathological characteristics were analyzed using the Chi-square test, Fisher's exact test, one-way ANOVA, and the Kruskal-Wallis test. Survival differences were evaluated using Kaplan–Meier survival curves and the log-rank test. Cox regression analysis was performed to identify independent prognostic factors, and nomograms were constructed to predict survival probabilities.ResultsPatients were divided into three groups based on sarcopenia and APR levels: Group 1 (80 cases), Group 2 (65 cases), and Group 3 (45 cases). Patients in Group 3 had longer progression-free survival (PFS) (HR = 0.403, p < 0.001) and overall survival (OS) (HR = 0.394, p < 0.001). APR-sarcopenia had the highest area under the curve (AUC) among all biomarkers, with predictive accuracy approaching that of the TNM staging. Multivariate Cox regression analysis identified pTNM, CA724, and APR-sarcopenia as independent prognostic factors for both PFS and OS. The nomograms for PFS and OS had C-index values of 0.794 (95% CI: 0.743–0.845) and 0.801 (95% CI: 0.751–0.851), respectively. Calibration analysis confirmed that the nomograms accurately predicted 3- and 5-year survival rates for PFS and OS.ConclusionsAPR exhibited superior prognostic accuracy for postoperative outcomes in gastric cancer patients compared to other hematological biomarkers. APR-sarcopenia demonstrated enhanced prognostic value and served as an independent prognostic marker. Additionally, APR-sarcopenia can help identify patients at high risk of metastasis and recurrence following gastric cancer surgery.